If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6b + -2 + -3b = 16 Reorder the terms: -2 + 6b + -3b = 16 Combine like terms: 6b + -3b = 3b -2 + 3b = 16 Solving -2 + 3b = 16 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 3b = 16 + 2 Combine like terms: -2 + 2 = 0 0 + 3b = 16 + 2 3b = 16 + 2 Combine like terms: 16 + 2 = 18 3b = 18 Divide each side by '3'. b = 6 Simplifying b = 6
| 5(6+8x)-7x=30-7x | | x*(x+1)=380 | | -24=12w | | 8(x-7)=3x-46 | | -8+4n=2(6-8n) | | (y+2)-y=2(y-1)+5 | | 3c^3-192=1 | | abs(-1+3x)=7x+4 | | 3(4k+5)=-27+6k | | 3/5x+2=6 | | 2y+3y=55 | | 4(4k+5)=-27+6k | | 3+4e= | | -8(8p+6)=8-8p | | 3+5e= | | 6-2(x+1)=42 | | 2x+1x=7 | | 12x-4=36 | | 6-4(n-1)=2n+4 | | 6(4x+2)+4x= | | 3(-7+3x)(-6-6x)= | | 18/7= | | 9x=3(7x+24) | | 3[x-1]=7 | | x+0.05(x)=9.70 | | graphy=-7x-13 | | (3x+13)+10= | | 8x^4-18x^2+8x^4=0 | | 1a^2+3a=-2 | | 2x-(3x/2)=4 | | 115=8/5x | | 3xsquared-7=69 |